Distribuição espacial e dinâmica populacional de Sphenophorus levis (Coleoptera: Curculionidae) em cana-de-açúcar - Izeppi, Tiago Sabongi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The knowledge of the population dynamics and insect distribution pattern in agricultural ecosystems is important for the development of more effective management strategies, assisting in better decision making. The objective of this work was to study the spatial distribution and population dynamics of Sphenophorus levis Vaurie (Coleoptera: Curculionidae) in sugarcane. In the study of spatial distribution, sampling was performed in 14 commercial areas of sugarcane, evaluating 100 sampling points per area through the trenches of 50 x 50 x 30 cm made in the line, for counting larvae, pupae, and S. levis adults and their damage, represented by the percentage of rhizomes damaged. In areas 6 to 14, at the time of sampling, baits were distributed for adult counts present outside the rhizomes. The spatial distribution was studied by geostatistical analysis. For the study of population dynamics, we used a commercial area of sugarcane in 2nd cut cultivated with SP81-3250 variety in the city of Américo Brasilense, SP. Monthly samples were taken through the opening 20 trenches in the cane row, 50 x 50 x 30 cm, for counting biological forms of pest present in the rhizome (larvae, pupae and adults). In the same occasion 20 baits were distributed in the area to count adults. The larvae, total biological forms (larvae + pupae + adults) and the damage S. levis were agregate, while pupae and adults distributed randomly in the field. The range of values obtained and the kriging interpolation maps showed large variability in insect populations and their damage in all studied areas. Based on the mid-range obtained for the variables studied, it is suggested that to estimate insect populations and their damage the sampling points should be spaced at 40 m. All the insect biological forms were found in the area during the year, however, the population peaks of adults occurred in rainy and warm time of year, in February and March, while larvae and pupae in more ...

O conhecimento da dinâmica populacional e do padrão de distribuição de insetos em ecossistemas agrícolas é importante para o desenvolvimento de estratégias de manejo mais eficazes, auxiliando em uma melhor tomada de decisão. O objetivo deste trabalho foi estudar a distribuição espacial e a dinâmica populacional de Sphenophorus levis Vaurie (Coleoptera: Curculionidae) em cana-de-açúcar. No estudo da distribuição espacial, foram realizadas amostragens em 14 áreas comerciais de cana-de-açúcar, avaliando 100 pontos de amostragem por área, através de trincheiras na linha de cana de 50 x 50 x 30 cm, para contagem de larvas, pupas e adultos de S. levis e de seus danos, representados pela porcentagem de rizomas danificados pela praga. Nas áreas 6 a 14, na ocasião da amostragem, foram distribuídas iscas para contagem dos adultos presentes fora dos rizomas. A distribuição espacial foi estudada através da análise geoestatística. Para o estudo da dinâmica populacional, foi utilizada uma área comercial de cana soca em 2° corte cultivada com a variedade SP81-3250, no município de Américo Brasilense, SP. Foram feitas amostragens mensais através da abertura de 20 trincheiras na linha de cana, de 50 x 50 x 30 cm, para contagem de formas biológicas da praga presentes no rizoma (larvas, pupas e adultos). Nas mesmas ocasiões foram distribuídas na área 20 iscas, para contagem dos adultos. As larvas, formas biológicas totais (larvas + pupas + adultos) e o dano de S. levis distribuíram-se de maneira agregada, enquanto pupas e adultos distribuíram-se aleatoriamente em campo. Os valores de alcance obtidos e os mapas de interpolação por krigagem mostraram grande variabilidade das populações do inseto e seu dano em todas as áreas estudadas. Com base no alcance médio obtido para as variáveis estudadas, sugere-se que para estimar as populações do inseto e seu dano em canaviais os pontos de amostragem devem ser...
Keywords: Cana-de-açúcar; Krigagem; Pragas agricolas; Inseto - População; Dinâmica populacional; Insect populations